COMPOSITE MATERIAL SEPARATION AND RECOVERY METHOD - TOKIMUNE AKIRA (2014)
PROBLEM TO BE SOLVED: To provide a composite material separation and recovery method for efficiently separating and recovering a composite material such as a laminate film of metal foil with less energy.SOLUTION: A composite material separation and recovery method for separating and recovering two or more types of thin-film materials from a composite material prepared by stacking the two or more types of thin-film materials selected from a thin-film material group consisting of various synthetic resin films, a synthetic resin sheet and metal foil via adhesives, includes at least: a crushing step of crushing the composite material into small pieces to obtain a crushed object; a thin-film material peeling step of bringing a permeable peeling agent solution into contact with the crushed object and peeling off the thin-film materials composing the composite material from each other to obtain a crushed mixture of the thin-film materials; and a separation and recovery step of separating the crushed mixture of the thin-film materials into a plurality of thin-film materials through separation processing based on a plurality of gravity separation operations using a plurality of gravity separation liquids different in specific gravity and recovering them.